Undergraduate Students’ Perception of Learner Autonomy Fostered through Google Classroom in Online Instruction - Nurdin, Magfirah; Anugerahwati, Mirjam; Wulyani, Anik Nunuk (Universitas Negeri Semarang, 2025)
The increasing use of online learning platforms such as Google Classroom has transformed how English as a Foreign Language (EFL) is taught and learned. However, limited research has explored students' perceptions of these platforms in promoting learner autonomy, especially in Indonesian higher education. This study aims to examine how undergraduate English education students view the role of Google Classroom in fostering learner autonomy during online classes. Using a descriptive quantitative approach, data were gathered through a structured Likert-scale questionnaire given to 30 students at a public university in Malang, Indonesia. The findings show that students generally hold positive perceptions, especially regarding their ability to take responsibility for their learning (M = 3.67), work independently (M = 3.43), and stay motivated (M = 3.50). They also reported active involvement in goal setting and personal study planning. These results suggest that Google Classroom offers a supportive environment for developing important aspects of learner autonomy. The study adds to the growing body of knowledge on digital learning by providing empirical evidence that structured online platforms can encourage autonomous learning behaviors in EFL settings.